Kasus Korupsi Sebagai Inspirasi Seni Stencil Graffiti di Media Akrilik - Wanis, Risa Azahro; Prasetyo, Abdul Rahman (Jurnal Pendidikan dan Penciptaan Seni, 2025)
In 2024, Indonesia was ranked 99th out of 180 countries with the highest level of corruption. It has become a serious, deeply rooted problem in the Indonesian system and has become a phenomenon that causes various concerns and anxieties among the public. One means of expressing criticism and anxiety about social issues is through graffiti art. This research project aims to describe the sources of ideas, the process of visualizing, and present the results of creating graffiti art. Using a method based on Alma M. Hawkins’ theory, this creation process involves three stages: 1) exploration of sources of ideas, 2) visual improvisation, and 3) formation/realization of the work. The result of this creation is six graffiti works on acrylic media using the stencil technique, representing six corruption cases in Indonesia. These works offer a new approach and innovation in the medium of graffiti art for expressing ideas. Additionally, these works can serve as an educational tool to raise public awareness about corrupt behavior and are hoped to provide criticism or perspective on corrupt behavior.